On the Burden of Proof in Civil Procedure - Keča, Ranko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The appliance of burden of proof rules is conceived of assumption that evidences are taken and that court didn’t reach the required degree of conviction of a particular fact, what implies limitation of application of these rules on proceedings in which the judgment is rendered after the plenary proceedings. The Code of Civil Procedure (CCP) has no suitable answers for the problems arising from new conception of the principle of party control of facts and means of proof in Serbian litigation legislature, by which the court has no more power to take the evidence ex offo. There is no answer to the question how should court conduct when evidence is not taken because of a lack of parties’ indication of the means of proof. In this case courts practice somehow wider conception of burden of proof rules, which however has no explicit legal ground. They are applying them even though evidences are not taken. In any case it would be useful to reformulate basic rule of burden of proof in manner which would correspondent to the new conception of the principle of party presentation. The rule of burden of proof applies when the high degree of conviction of facts is demanded from the court, in order to render the judgment. Consequently this rule loses its’ sense when mere probability of factual findings is demanded. The broader conception of parties’ representation principle however does not liberate court from his responsibility to clarify facts that should be base for adjudication. Circumstance that CCP does mention the principle of material truth anymore should not be seen as argument for liberation of mentioned responsibility. It is still expected from the court to be active. Only when joint effort of the court and parties is left without of goal, in sense that court doesn’t reach the high degree conviction, there would be ground for burden of proof rule’s application. In this situation court also must justify why he couldn’t reach required degree of conviction, i.e. he must give clear reasons for the cause of application of burden of proof rules. Thus the role of the court is not relieved, nor does the application of burden of proof provisions mean the liberation from the duty to evaluate the evidences and reasoning the impossibility of reaching the required degree of conviction. In the case when evidences are not taken at all the application of burden of proof rule could be only justified with the idea that else unacceptable results would arise – substantive legal protection and favouritism of the party who didn’t make any effort to proof its factual allegations.